Customer perception about corporate social responsibility in the Telecommunication Industry - Kusi, Daniel Boateng (2016)
A Thesis Submitted to the Department of Marketing and Corporate Strategy, Kwame Nkrumah University of Science and Technology in Partial Fulfillment of the Requirement for the Degree of Master of Business Administration (Marketing Option),